Fractionation of a hydrocolloid emulsifier reclaimed from winery waste. (15th December 2019) - Pavlou, Alexandros; Panayiotou, Costas; Kalogianni, Eleni P.; Georgiou, Despoina; Ritzoulis, Christos
Highlights: A natural emulsifier is extracted from wine processing waste. The natural extract is fractionated via preparative size exclusion chromatography. The natural emulsifier consists of 4 main molecular populations of different MW. The chemical composition and surface activity of each population is assessed. This information is used as to model the collective action of the composite extract. Abstract: Complex hydrocolloids have been isolated and fractionated using a consecutive elution process, starting from winery waste. These extracts consist mainly of polysaccharidic populations and of smaller protein molecules and they exhibit emulsifying, thickening and texture-modifying activity. This work is a systematic study of these individual populations, as fractionated with preparative size exclusion chromatography (Prep-SEC) in terms of their chemical identity, surface properties, and emulsification behavior. The fractions have been characterized via SEC-MALLS, FTIR, DLS, zeta potential, and interfacial tension measurements. The results highlight the antagonistic and synergistic effects of the individual components of the above-mentioned complex natural material (winery waste extract) towards its emulsifying behavior, and provide a model for the kinetics of the evolution of a Pickering interfacial layer.